Social Self-Efficacy Reducing Fear of Missing Out (Fomo) to Improve Life Satisfaction Among Students in Thailand - Utaminingsih, Sri; Anwar, Saiful; Puji Lestari, Yulita (Wahana Dedikasi: Jurnal PkM Ilmu Kependidikan, 2025)
The phenomenon of Fear of Missing Out (FoMO), which has increased alongside the rapid development of digital technology and social media use, poses a significant psychosocial challenge among university students. FoMO is characterized by anxiety arising from the feeling of being left out of social experiences enjoyed by others, contributing to increased social stress, academic concentration disturbances, and a decline in overall life satisfaction. This study aims to explore the role of social self-efficacy—an individual’s belief in their ability to interact and build social relationships—in reducing FoMO and enhancing life satisfaction among students in Thailand through a community service program conducted by graduate students from the Educational Management Study Program at Universitas Pamulang at Sholahuddin School, Thailand. A qualitative approach was employed, with data collected through participatory observation, focus group discussions, in-depth interviews, and direct observation of social dynamics during the program. The results indicate that students with high social self-efficacy are better able to manage social pressures and social media expectations, effectively reducing FoMO. Moreover, strengthening real social interactions and local cultural values such as solidarity, harmony, and mutual respect enhances psychological resilience and improves life satisfaction. This study underscores the importance of developing social skills through culturally-based training and community interventions as an effective strategy to support the mental health and psychological well-being of students in a digital era full of social pressures Keywords : Social self-efficacy, Fear of Missing Out (FoMO), life satisfaction, students, social interaction, local culture, psychological well-being, community service, social media.